2011
DOI: 10.1021/jp201150q
|View full text |Cite
|
Sign up to set email alerts
|

Ion Pairing in Aqueous Electrolyte Solutions with Biologically Relevant Anions

Abstract: We performed molecular simulations to study ion pairing in aqueous solutions. Our results indicate that ion specific interactions of Li(+), Na(+), and K(+) with the dimethyl phosphate anion are solvent-mediated. The same mechanism applies to carboxylate ions, as has been illustrated in earlier simulations of aqueous alkali acetate solutions. Contact ion pairs play only a minor role--or no role at all--in determining the solution structure and ion specific thermodynamics of these systems. On the basis of the Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 25 publications
(64 reference statements)
1
61
0
Order By: Relevance
“…The problem is not trivial, even at infinite dilution with respect to the solute where subtle competition between solute-water and water-water interactions exists. This and similar problems have recently been studied in molecular dynamics simulations by detailed force-field modeling, [7][8][9][10][11][12][13][14][15][16][17][18][19] as also by the integral equation technique. 20 Temperature is considered to be the most important thermodynamic parameter and the ability of water to solvate a solute depends on it.…”
Section: Introductionmentioning
confidence: 97%
“…The problem is not trivial, even at infinite dilution with respect to the solute where subtle competition between solute-water and water-water interactions exists. This and similar problems have recently been studied in molecular dynamics simulations by detailed force-field modeling, [7][8][9][10][11][12][13][14][15][16][17][18][19] as also by the integral equation technique. 20 Temperature is considered to be the most important thermodynamic parameter and the ability of water to solvate a solute depends on it.…”
Section: Introductionmentioning
confidence: 97%
“…17 These apparent contradictions are not only limited to their relative ordering, but also on the type of interactions, in particular, the ion-pairs 18 formed between the cations and the carboxylic acid moiety, which include solventseparated (2SIP), solvent-shared (SIP), contact-ion pairs (CIP), and/or bound complexes. 11,[15][16][17]19 A potential explanation for this contrasting behavior, at least in terms of ion affinity, is hinted by simulations from Schwierz et al, 20 which suggest that the relative ordering of the cations depends on the concentration of ions as well as on solution pH. At certain conditions, even a complete reversal of the Hofmeister ordering would be expected (from Li + 4 Na + 4 Cs + to Cs + 4 Na + 4 Li + ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, specifically in terms of electrochemical applications, the suppression and modification of ion pair formation is highly desirable. 12 In general, one can distinguish between contact and solvent-separated ion pairs, 1,3,13,14 while the mechanisms leading to the formation of these aggregates are still under debate. 1,14,15 Previous results demonstrated that the solvent itself as well as the solvent chemical activity 1,16,17 strongly influence many effects, e.g.…”
Section: Introductionmentioning
confidence: 99%